The development of a business model innovation framework from a value network perspective applied to the prospective cemented tungsten carbide additive manufacturing sector in South Africa - Van Heerden, Ane (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.